Enabling service co-production: a theory-building case study. Issue 4 (4th July 2019) - Grace, Audrey; Gleasure, Rob; Finnegan, Patrick; Butler, Tom
ABSTRACT: Service co-production between professionals and customers is an increasingly popular alternative to traditional "off the shelf" models of service delivery. There is, however, little empirical research describing how services are co-produced with individual customers, nor the most suitable roles for IS/IT in this co-production. This study unpacks how services are co-produced by developing a substantive Theory of Service Co-Production activities (and mediating contextual factors) in the financial services sector. A two-phase theory-building approach is employed. First, a preliminary model is derived based on Activity Theory and extant research. Second, this preliminary model is refined and elaborated upon through an extensive empirical analysis of the co-production of financial services. The study further reveals four key contradictions driving service co-production. These contradictions highlight the incomplete alignment of motives and goals between service professionals and customers, as well as the trickle-down IS/IT impact of this misalignment. The study concludes by discussing the enabling and constraining influence of IS/IT in service co-production.